Studi Simulatif Pengaruh Sudut Kemiringan Sudu, Tip Speed Ratio dan Soliditas terhadap Faktor Daya Turbin Darrieus Dengan Profil Sudu NACA0021 - Muhammad, Abdulkadir; Harianto,; Rudy Hartana, Dandung (ReTII, 2019)
Performance of Darrieus turbines are influenced by many fators, among them are blade profile, blade angle of inclination (Î±), tip speed ratio (Î»), and blade solidity (Ïƒ). The objective of the research is to investigate the influences of Î±, Î», and Ïƒ to the power factor (Cp) of a vertical Darrieus water turbine by mean of CFD FLUENT simulation. The simulation has been conducted in a 20 cm rotor diameter, 25 cm rotor length, 3 blades, NACA0021 blade profile vertical Darrieus water turbine. Blade lenght variations are 4 cm, 5 cm and 6 cm; blade angle of inclinatian variations are 00, 50 and 100; and rotor speed variations are 60 rpm, 80 rpm, 100 rpm, 120 rpm, 150 rpm, and 200 rpm. It is concluded from the research that maximum Cp is 3.2609 % achieved at Ïƒ = 0.9, Î» = 1.0467 and Î± = 50.